‘Drumbeat of war’: Hearing spiritual warfare through Pentecostal musicking - Ajose, Toyin Samuel (Journal of Pentecostal and charismatic Christianity, 2025)
Spiritual warfare in Pentecostal theology is ubiquitous with war metaphors. Despite scholarly engagements with Charismatic teachings and practices of spiritual warfare, how Pentecostals construct, reinforce and circulate spiritual warfare messages through their music is yet to be fully known. In this study, I interrogate the role of music in framing and sustaining spiritual warfare theology among Pentecostal Christians. I ask, how are spiritual warfare themes shaped and are being shaped through Pentecostal musicking? What are the sonic–musical and non-musical–approaches utilized by Pentecostal musicians to emphasize these themes in worship? Data for the study were gathered from live video recordings of two songs: ‘Song of Angels’ and ‘Fragrance to Fire’ by Dunsin Oyekan – a famous Nigerian Pentecostal music minister. By engaging conceptual and analytical frameworks from musicology, anthropology of religion and Pentecostal studies, I argue that Pentecostal musicking provides the discursive site for hearing how embodied and sonic practices serve as weapons for people to fight and win battles –spiritual and existential –by playing the ‘drumbeat of war’.